Effects of Baobab fruit powder on gut and cardiometabolic health in obesity—Protocol for a randomised placebo-controlled trial - Sylvia Riedel; Keren de Buys; Abegail M. Tshivhase; Amy E. Mendham; Pieter Venter; Fatima Hoosen; Lara R. Dugas; Caroline D’Alton; Jody A. Rusch; Bianca Southon; Carmen P. Pheiffer; Rabia Johnson; et al. (PLoS ONE, 2025)
Despite its commercial availability, its high fibre, vitamin C and polyphenol content, there are limited scientific studies exploring the cardiometabolic effects of Baobab fruit powder (BFP) in humans. Due to its high fibre content, BFP may offer a potential intervention to reduce intestinal barrier dysfunction and therefore mitigate cardiometabolic risk. A randomized, double-blind, placebo-controlled trial will be conducted with 50 apparently healthy participants living with obesity. Participants will consume either 16 g of BFP or an isocaloric placebo daily for 45 days. The primary outcome will be intestinal permeability determined using the urinary lactulose/mannitol test. Secondary outcomes include blood biomarkers in intestinal permeability (lipopolysaccharide (LPS), intestinal fatty acid binding protein (IFABP), soluble cluster of differentiation 14 (sCD14) and LPS-binding protein (LBP)), microbiota diversity and composition and cardiometabolic risk markers including glucose levels, blood lipid profiles and blood pressure. Liver and kidney function will be monitored at baseline, after 2 weeks and following 45 days of consumption as safety outcomes. The study protocol ensures rigorous, weekly monitoring of participant compliance and tolerability, along with careful tracking of potential adverse events. Intention-to-treat analysis and mixed effects models will be employed for statistical analyses. Potential selection bias and participant dropout are addressed through thorough recruitment strategies and predefined sample size calculations. This research will contribute to the growing body of knowledge on dietary interventions in the context of cardiometabolic risk, particularly in populations at risk for developing metabolic disease. South African Clinical Trial Registry - SANCTR, DOH-27-062024-8061; Pan African Clinical Trial Registry – PACTR202308727853680